Persepsi Mahasiswa Prodi Teknologi Pangan Mengenai Keterkaitan Program Program Merdeka Belajar Kampus Merdeka Dengan Kompetensi Lulusan - Sarah Giovani; Maryam Jameelah; Nafisah Eka Puteri; Ema Komalasari; Afiya Deliana Putri (Universitas Al Azhar Indonesia, 2022)
The MBKM program is a program to prepare graduates who are ready to work with areas of expertise and the needs of the world of work. The purpose of this study was to determine the perception of students, especially students of the Food Technology Study Program, Al-Azhar University, Indonesia, on the relationship between the MBKM program and the competencies of graduates that must be possessed in the future, or post-lecture period. The data source is obtained from an online survey conducted by the Ministry of Education, Culture, Research, and Technology Directorate General of Higher Education by involving 25 students of the Food Technology Study Program. The perceptions of those students towards the realm of graduate competence after participating in the MBKM program are: (1) the MBKM program is considered very useful, (2) The improvement of soft skills for graduates shows that there is a fairly good improvement, (3) MBKM activities are quite important in preparation for the post-campus period, (4) MBKM activities are by the needs of graduates, (5) Interested and intend to choose internships or work practices as learning activities outside the study program of interest.Keywords - Food Technology, Graduates, Learning outcomes, MBKM Program, Perception